Determinants of Dividend Smoothing: Empirical Evidence - Leary, Mark T.; Michaely, Roni (Review of Financial Studies, 2011)
We document the cross-sectional properties of corporate dividend-smoothing policies and relate them to extant theories. We find that younger, smaller firms, firms with low dividend yields and more volatile earnings and returns, and firms with fewer and more disperse analyst forecasts smooth less. Firms that are cash cows, with low growth prospects, weaker governance, and greater institutional holdings, smooth more. We also document that dividend smoothing has steadily increased over the past 80 years, even before firms began using share repurchases in the mid-1980s. Taken together, our results suggest that dividend smoothing is most common among firms that are not financially constrained, face low levels of asymmetric information, and are most susceptible to agency conflicts. These findings provide challenges and guidance for the developing theoretical literature.